Posterior Condylar Cartilage Thickness and Posterior Condylar Offset of the Femur: A Magnetic Resonance Imaging Study. (April 2016) - Wernecke, Gregory C; Seeto, Bradley G; Chen, Darren B; MacDessi, Samuel J
Purpose: To measure the femoral posterior condylar cartilage (PCC) thickness and the posterior condylar offset (PCO) and determine the correlation between the 2 parameters in 530 normal subjects using magnetic resonance imaging (MRI). Methods: Records of 287 male and 243 female patients (mean age, 40.7 years) who underwent MRI for traumatic soft tissue knee injuries not involving the femoral PCC and did not have symptomatic knee arthritis were reviewed. Results: The PCC thickness was comparable in the lateral and medial sides (2.04 vs. 1.99 mm, p=0.13). Males had thicker PCC in the medial (2.05 vs. 1.92 mm, p=0.0006) and lateral (2.16 vs. 1.86, p<0.0001) sides than females. Age did not correlate with PCC thickness. The bony PCO was larger in the medial than lateral side (25.8 vs. 22.6 mm, p<0.0001). Males had a larger PCO than females in the medial side only (26.1 vs. 25.5 mm, p = 0.0195). The bony PCO did not correlate with PCC thickness. Conclusion: Femoral PCC thickness was comparable in the medial and lateral sides. Males had thicker PCC in the medial and lateral sides than females.